Mdm2-Mediated Downmodulation of GRK2 Restricts Centrosome Separation for Proper Chromosome Congression - Reglero, Clara (Cells, 2021)
The timing of centrosome separation and the distance moved apart influence the formation of the bipolar spindle, affecting chromosome stability. Epidermal growth factor receptor (EGFR) signaling induces early centrosome separation through downstream G protein-coupled receptor kinase GRK2, which phosphorylates the Hippo pathway component MST2 (Mammalian STE20-like protein kinase 2), in turn allowing NIMA kinase Nek2A activation for centrosomal linker disassembly. However, the mechanisms that counterbalance centrosome disjunction and separation remain poorly understood. We unveil that timely degradation of GRK2 by the E3 ligase Mdm2 limits centrosome separation in the G2. Both knockout expression and catalytic inhibition of Mdm2 result in GRK2 accumulation and enhanced centrosome separation before mitosis onset. Phosphorylation of GRK2 on residue S670 enables a complex pattern of non-K48-linked polyubiquitin chains assembled by Mdm2, which correlate with kinase protein degradation. Remarkably, GRK2-S670A protein fails to phosphorylate MST2 despite overcoming Mdm2-dependent degradation, which results in defective centrosome separation, shorter spindles, and abnormal chromosome congression. Conversely, extra levels of wild-type kinase in the G2 cause increased inter-centrosome distances with longer spindles, also converging in congression issues. Our findings show that the signals enabling activity of the GRK2/MST2/Nek2A axis for separation also switches on Mdm2 degradation of GRK2 to ensure accurate centrosome dynamics and proper mitotic spindle functionality.